TEICHMANN TEST: ASSESSMENT OF HEMOGLOBIN CRYSTALS ON BLOOD SPOTS EXPOSED TO POWDER DETERGENT - Abid, Istiana Firqah; Rezakola, Erik; Hanura, Imam Yusuf (Universitas Airlangga, 2024)
Evidence found at the crime scene (TKP) in the form of bloodstains needs to be examined to ensure that the evidence is really blood so that it can assist the investigation process. However, in some cases, criminals can remove or remove bloodstains using detergents that are used daily which contain surfactants. The purpose of this study was to find out how to examine and describe hemoglobin crystals in blood spots exposed to several powder detergents using the Teichmann test. This study used an experimental method using 3 different brands of detergent with 2 controls, namely a positive control with the presence of blood spots and a negative control without blood spots. The examination results obtained positive control results in all experiments as much as 100% still giving a brown rhombus-shaped appearance of hemoglobin crystals like needles even though the blood spots had been exposed to powder detergent. Keywords: Blood spot, Detergent, Hemoglobin, Teichmann test